2018
DOI: 10.26633/rpsp.2018.174
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating policy responses to noncommunicable diseases in seven Caribbean countries: challenges to addressing unhealthy diets and physical inactivity

Abstract: Objective. To identify, assess, and compare existing policies on noncommunicable diseases (NCDs) in the Caribbean, gaps in policy responses, and the factors influencing successful policy development and implementation following the Port of Spain Declaration of 2007. Specifically, to examine policies that target the upstream determinants of two NCD risk factors—unhealthy diets and physical inactivity. Methods. A total of 76 semi-structured interviews with 80 relevant sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…Investigators believed that there is not a clear national research agenda and that there is not enough local research to address national health problems. This assessment of the national research landscape speaks to the challenges within the current environment to meet the needs of stakeholders, which are consistent across the Caribbean (14). A government lead research agenda can facilitate prioritizing of research needs, advocates for partnerships and buy in from stakeholders to promote meaningful change (11,15,16).…”
Section: Local Researchmentioning
confidence: 81%
“…Investigators believed that there is not a clear national research agenda and that there is not enough local research to address national health problems. This assessment of the national research landscape speaks to the challenges within the current environment to meet the needs of stakeholders, which are consistent across the Caribbean (14). A government lead research agenda can facilitate prioritizing of research needs, advocates for partnerships and buy in from stakeholders to promote meaningful change (11,15,16).…”
Section: Local Researchmentioning
confidence: 81%
“…This type of support is likely to be particularly important for those smaller countries with the least capacity for developing and implementing policy. This relationship is explored further in two papers in this supplement, by Murphy et al (19) and by Kirton et al (22).…”
Section: Discussionmentioning
confidence: 93%
“…Health in All Policies remains a concept that has yet to be institutionalized. These issues are addressed in the paper in this supplement by Murphy et al (19).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…An evaluation of the Port of Spain Declaration in 2018 found that taking effective measures to address the distal (or upstream) determinants of an unhealthy diet and physical inactivity (e.g. cultural and environmental conditions) remained challenging, 8 although new initiatives, such as taxing sugar-sweetened beverages, were being implemented.…”
Section: Introductionmentioning
confidence: 99%